The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s00227-007-0787-9
|View full text |Cite
|
Sign up to set email alerts
|

Methodology of light response curves: application of chlorophyll fluorescence to microphytobenthic biofilms

Abstract: The light response curve methodology for microphytobenthic biofilms was studied by comparing the two most usual approaches used in pulse amplitude modulated (PAM) fluorometry. The non-sequential light curve (N-SLC) method is characterized by independent measures of the photosynthetic activity across a light gradient whereas the rapid light curve (RLC) method consists of successive measures on the same sample exposed to a stepwise increase of light intensities. Experiments were carried out on experimental micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 61 publications
2
64
0
Order By: Relevance
“…In a number of papers [8e10], it is noted that an increase in the illumination intensity leads to a decrease in the phytoplankton's fluorescence because it is bound to increase the amount energy used in cells for a photosynthesis that, as a result, causes photochemical quenching and structural changes in the of chloroplasts. In reference [8], it is shown that, at critical values of the illumination intensity, the fluorescence reaches a maximum or minimum level, and further increases or decreases in the illumination intensity do not lead to further increases or decreases in the fluorescence.…”
Section: Theorymentioning
confidence: 98%
“…In a number of papers [8e10], it is noted that an increase in the illumination intensity leads to a decrease in the phytoplankton's fluorescence because it is bound to increase the amount energy used in cells for a photosynthesis that, as a result, causes photochemical quenching and structural changes in the of chloroplasts. In reference [8], it is shown that, at critical values of the illumination intensity, the fluorescence reaches a maximum or minimum level, and further increases or decreases in the illumination intensity do not lead to further increases or decreases in the fluorescence.…”
Section: Theorymentioning
confidence: 98%
“…The relative electron transport rate (rETR) was calculated as follows: rel rETR ¼ ΔF=F 0 m Á E Á 0:5 because it is assumed that light energy is equally distributed between both photosystems (Perkins et al 2006;Herlory et al 2007). Photosynthetic electron transport rate curves were fitted by means of an automatic spreadsheet based on linear regression for estimating ETR per light intensity and a Chisquare minimisation for the exponential function ETR= ETR max (1−e −α E/ETRmax ) proposed by Webb et al (1974, in Henley 1993.…”
Section: Determination Of Photosynthetic Characteristicsmentioning
confidence: 99%
“…It should be noted that during RLCs, F ' does not reach steady-state, and thus RLCs are a compromise measurement used in situ to minimize errors induced by migration and artifacts induced by the experimental method (e.g. Perkins et al 2006, Herlory et al 2007). Following Schreiber et al (1994), the rETR is then given by rETR = Φ PSII × E × 0.5, where E is the actinic irradiance (µmol photons m …”
mentioning
confidence: 99%